2015
DOI: 10.1002/ajh.24191
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for myelofibrotic transformation among 272 Chinese patients with JAK2‐mutated polycythemia vera

Abstract: Post-polycythemia vera myelofibrosis (post-PV MF) is a critical hematologic evolution of polycythemia vera (PV). The main purpose of the present study was to identify the possible risk factors for the occurrence and prognosis of post-PV MF in Chinese patients with PV. A cohort of 272 Chinese PV patients with JAK2 V617F or exon12 mutation was retrospectively analyzed. Of the 272 patients with PV, 63 developed post-PV MF. Platelet count >550 3 10 9 /L and splenomegaly were identified as independent risk factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
1
14
0
1
Order By: Relevance
“…MPNs mainly include polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF) . Thrombosis, leukemic transformation, and myelofibrotic transformation are critical complications of MPN and are highly common in patients with MPN . Fatalities due to thrombosis account for 35%~70% of the total mortality rate of MPN, making it the most important risk factor affecting event‐free survival and overall survival (OS) of MPN patients …”
Section: Introductionmentioning
confidence: 99%
“…MPNs mainly include polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF) . Thrombosis, leukemic transformation, and myelofibrotic transformation are critical complications of MPN and are highly common in patients with MPN . Fatalities due to thrombosis account for 35%~70% of the total mortality rate of MPN, making it the most important risk factor affecting event‐free survival and overall survival (OS) of MPN patients …”
Section: Introductionmentioning
confidence: 99%
“…When we combined risk levels to establish a range of possible OS levels, our model provided an OS range of 14.2 to 17.3 LY depending on age and baseline JAK2. Only the study by Bai et al 19 had an OS (17.5 LY) that slightly fell outside of the modeled OS range.…”
Section: Discussionmentioning
confidence: 82%
“…The results of the validation indicated a good correspondence between the model and the published observational studies available for comparisons. The mean OS in the published observational studies 19 , 31 , 32 that was included in the validation of the model was 14.9 to 17.5 years over a 20-year time horizon. When we adjusted our model’s baseline age and baseline JAK2 burden to match the studies’ variables, our model predicted a mean OS that ranged between 15.0 to 16.5 years.…”
Section: Discussionmentioning
confidence: 99%
“…To date, sex is not included among risk factors for PV evolution into PPV-MF and BP. Conventional risk factors for PPV-MF and BP transformation include age ≥ 60 years, leukocytosis (≥ 15-30 × 10 9 /L), homozygosity for JAK2 mutation, and exposures to alkylating agents (reviewed by Cuthbert D et al) [103][104][105][106][107][108][109][110]. NGS based studies demonstrated also that non-driver mutations in myeloid genes could influence PV evolution: ASXL1, SRSF2, RUNX1, SF3B1, and IDH1/2 for PPV-MF; ASXL1, TP53, SRSF2, IDH1/2, and RUNX1 for BP [110].…”
Section: The Controversial Role Of Female Sex On Pv Survivalmentioning
confidence: 99%